Efektivitas Model Pembelajaran Think Talk Write (TTW) Terhadap Kemampuan Literasi Numerasi Matematika Siswa Kelas VIII - Oktavia, Lisa; Susetyawati, MM Endang; Kintoko, Kintoko (Indo-MathEdu Intellectuals Journal, 2024)
The TTW learning model is a discovery model which includes thinking, speaking, and writing activities. This research was conducted with the aim of seeing the effectiveness of the TTW learning model in terms of the mathematics numeracy literacy abilities of class VIII students. This quantitative research uses a Quasi Experimental method with a one group posttest design. The population in this study were all class VIII students of SMP N 1 Bambanglipuro. The technique used is simple random sampling to determine the control class and experimental class. Class VIIIF has 27 students as the control class and class VIIIA has 27 students as the experimental class